Siswa Indonesia Darurat Kompetensi dan Karakter, Pemerintah Ciptakan Profil Pelajar Pancasila Sebagai Solusi - Sihombing, Prima; Hairani Siregar (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
Recently, there are different types of problems that occur in school environments, ranging from the increasingly declining grades and morals of the student, the student's ability to adapt to technological progress, or the student who is less skilled at solving the problems that arise around him. So, the ministry provides Pancasila Student's Profiles as a form of hope, purpose, and reference to national education and as a reference by the educator in building student’s competence and character. By implementing the Pancasila Student's Profiles at school, students are expected to become lifelong learning who are competent, have character, and behave according to Pancasila values. This study aims to observe whether the Pancasila Student's Profiles has an impact on increased competence and character building in UPT SDN 060886 Titi Rantai, using a qualitative approach so that the situation or phenomena that occurr in school can be described clearly and deeply, and the meaning of the phenomenon can be well analyzed. Studies indicate that the Pancasila Student's Profiles has not been able to overcome the problems of student’s competence and character.